PKM Pemberdayaan Ibu Rumah Tangga Pesisir Pantai Panrangluhu Melalui Pelatihan Pembuatan Briket Arang Dengan Nilai Jual Tinggi dan Ramah Lingkungan - Satria Gunawan Zain; Kurnia Prima Putra; Edy, Marwan Ramdhany (Jurusan Teknik Informatika dan Komputer, 2023)
This article discusses the Community Service (PKM) program which aims to empower housewives in the coastal area of Panrangluhu Beach through training in making charcoal briquettes from coconut shells. This activity is carried out with a focus on the creation of charcoal briquette products with high selling value and environmentally friendly. The main objective of this program is to improve the skills of housewives in making charcoal briquettes, improve the economic aspects of families through increasing income from the sale of charcoal briquettes, and at the same time support efforts to preserve the coastal environment. The methodology of implementing the program involves technical training in making charcoal briquettes and education on sustainable environmental aspects. In this training, housewives are trained to identify and use environmentally friendly local raw materials, as well as understand the importance of sustainable natural resource management. The result of this program is an increase in the knowledge and skills of housewives in producing high-quality charcoal briquettes, which can then be sold at more favorable prices. It is hoped that this PKM program will provide dual benefits, namely improving the standard of living of Panrangluhu Beach coastal housewives through increasing income and at the same time encouraging environmental awareness in the use of natural resources. In addition, the application of environmentally friendly practices in the production of charcoal briquettes can also contribute to the preservation of vulnerable coastal ecosystems.